PENGARUH PEMBERIAN JUS BUAH NANAS (ANANAS COMOSUS) TERHADAP PENYEMBUHAN LUKA PERINEUM PADA IBU NIFAS DI KLINIK SUMIARIANI MEDAN JOHOR KABUPATEN DELI SERDANG TAHUN 2025 - Sitepu, Stefani Anastasia; Hutabarat, Vitilina (JURNAL ILMIAH DHDT - KEBIDANAN, 2025)
Perineal wounds are one form of trauma that is often experienced by postpartum mothers, both those that occur naturally or due to episiotomy. The wound healing process is influenced by varios factors, one of which is nutritional intake. The bromelain enzyme in pineapple (Ananas Comosus) is know to have anti-inflammatory, analgesic, and antibacterial properties, so it can accelerate wound healing. This study aims to determine the effects of giving pineapple juice on the healing process of parineal wounds in postpartum mothers at the Sumaiariani Clinic, Medan Johor, Deli Serdang Regency. The method used in this study was quantitative with a pre-experimental design and a one group pretest-posttest approach, involving 20 postpartum mothers as respondents with grade l and ll perineal wounds. Pineapplke juice was given for seven consecutive days, twice a day. Data were collected using an observation sheet based on the REEDA score to evaluate Changes in wound healing conditions between before and after the intervention was given. Data alanysis was carried out using the Wilcoxon test to see significant differences between conditions before and after pineapple juice administration. The results showed a siginificant difference in REEDA scores before and after the intervention, with a p value <0.005. This indicated that pineapple juice it has effectiveness in supporting the acceleration perineal wound recovery. Thus, the administration of pineapple juice demonstrates real effectiveness in supporting healing process, and it can be used as safe natural therapy opyion without the use of drugs to plays a role in supporting the regeneration of perineal wound tissue.